PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS V SD NEGERI 25 LUBUKLINGGAU - Pregina Miranda; Ani Fiani; Angga Bagus Kusnanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the Implementation of the Make A Match Learning Model in Indonesian Language Learning for Fifth Grade Students of SD Negeri 25 Lubuklinggau. This research method is pre-experimental, with the design used is one-group pretest-posttest design. The population in this study were all fifth grade students of SD Negeri 25 Lubuklinggau. Sampling was done using saturated sampling technique, namely in fifth grade of SD Negeri 25 Lubuklinggau totaling 26 students as a sample class. Data collection techniques using multiple choice tests. Data analysis techniques with steps: normality test and z test. Based on the results of the z-test analysis with a confidence level obtained α = 0.05 data z count = 5.34 and z table = 1.64 then the data shows that the z count value> z table. The average value of student pretest is 42.77 and the average value of posttest is 80.31, so it can be said that H0 is rejected and Ha is accepted. Thus, it can be concluded that the application of the Make A Match learning model in Indonesian language learning for fifth grade students at SD Negeri 25 Lubuklinggau was significantly completed.